Collaborative learning practices: teacher and student perceived obstacles to effective student collaboration. Issue 1 (2nd January 2018) - Le, Ha; Janssen, Jeroen; Wubbels, Theo
Abstract: While the educational literature mentions several obstacles affecting the effectiveness of collaborative learning (CL), they have often been investigated through the perceptions of only one actor, either teachers or students. Therefore, some sources of obstacles that teachers and students encounter may not have been revealed. In this study, 19 teachers and 23 students in different disciplines at a pre-service teacher education faculty at a university in Vietnam were interviewed. In total, 47% of the teachers taught science subjects and 53% taught social subjects; 35% of the students majored in science subjects, 57% in social subjects, and 8% in primary education. With regard to study cohorts, 22% of the students were in the first and second year while 78% were in the third and fourth year of their four-year bachelor's programme. These programmes produce qualified teachers for primary and secondary schools nationwide. Based on grounded theory analysis, four common obstacles to collaboration were identified: students' lack of collaborative skills, free-riding, competence status, and friendship. Furthermore, the results showed three interrelated antecedents that contribute to these obstacles. Central to the antecedents is the strong focus of the teachers on the cognitive aspects of CL, which led the participating teachers to neglect the collaborative aspects of CL. These antecedents were demonstrated in the ways teachers set CL goals, provided instruction, and assessed student collaboration. This study may be useful for educators, designers, and researchers to foster the quality of student collaboration.